2002
DOI: 10.4049/jimmunol.169.3.1197
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactive Antigen Is Required to Prevent Erosion of Established T Cell Memory and Tumor Immunity: A Heterologous Bacterial Model of Attrition

Abstract: Induction and maintenance of T cell memory is critical for the control of intracellular pathogens and tumors. Memory T cells seem to require few “maintenance signals,” though often such studies are done in the absence of competing immune challenges. Conversely, although attrition of CD8+ T cell memory has been characterized in heterologous viral models, this is not the case for bacterial infections. In this study, we demonstrate attrition of T cell responses to the intracellular pathogen Listeria monocytogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 64 publications
6
31
1
Order By: Relevance
“…It has been previously shown that viral infections induce erosion of established preexisting CD8 ϩ T cell memory (4,5). This erosion of established memory is not restricted to viral challenges as we have previously reported that infection of mice with the intracellular bacterium BCG also results in erosion of established CD8 ϩ T cell memory (29). Several conclusions can be drawn from our results.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It has been previously shown that viral infections induce erosion of established preexisting CD8 ϩ T cell memory (4,5). This erosion of established memory is not restricted to viral challenges as we have previously reported that infection of mice with the intracellular bacterium BCG also results in erosion of established CD8 ϩ T cell memory (29). Several conclusions can be drawn from our results.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, erosion of CD8 ϩ T cell memory was irreversible as removal of the heterologous chronic pathogens (ST and BCG) with antibiotics did not restore the relative numbers of memory CD8 ϩ T cells. We have previously reported that such erosion of CD8 ϩ T cell memory results in compromised protection against a challenge with OVA-expressing tumor cells highlighting the functional consequences of erosion of OVA-specific CD8 ϩ T cell memory (29). Our results now indicate that erosion of established memory also results in compromised protection against pathogen rechallenge.…”
Section: Discussionsupporting
confidence: 67%
“…The generalization of these observations has, however, yet to be demonstrated, and most models of clonal attrition involve viral or bacterial infections with rapid and extensive expansion of highly immunodominant T cell clones [9,10]. To date, the relative importance of these issues in the context of chronic parasitic infections has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…However, such situations may have limited physiological importance. In a contrasting study, intermittent stimulation by persisting antigen was shown to be necessary for CD4 + memory T cell survival [7], although again competition from other T cells was not taken into account.In addition to the possible role of antigen in maintaining CD4 + T cell memory, a number of studies have suggested that the memory T cell compartment itself is of finite size, opening the way for inter-clonal competition for space within this compartment [2,8].The generalization of these observations has, however, yet to be demonstrated, and most models of clonal attrition involve viral or bacterial infections with rapid and extensive expansion of highly immunodominant T cell clones [9,10]. To date, the relative importance of these issues in the context of chronic parasitic infections has been largely ignored.…”
mentioning
confidence: 99%
“…1B). In contrast, LCMV-specific memory cells, identified by their production of IFN-␥ in response to the LCMV peptides NP396 396 -404 , gp33 [33][34][35][36][37][38][39][40][41] , and gp276 276 -286 , were concentrated in the CFSE high subset of CD44 high cells that had participated in only limited rounds of division (Fig. 1B).…”
Section: Limited Homeostatic Reconstitution By Lcmv-specific Memory Cmentioning
confidence: 99%